Peningkatan Pemahaman Siswa terhadap Potensi dan Pemanfaatan Ekonomi Digital dalam Mendukung Bisnis UMKM - Anggi Pratiwi Sitorus (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to see the Improvement of Students' Understanding of the Potential and Utilization of the Digital Economy in Supporting MSME Businesses. Through this community service activity, we aim to improve students' understanding of the concept, potential, and utilization of the digital economy to support Micro, Small, and Medium Enterprises (MSMEs). The method in this study is using Surveys and interviews. The variables used in this study are MSMEs, digital platforms and students. The results of this research activity show a significant increase in students' understanding and skills, which is reflected in their abilities.